Analisis Kepastian Hukum Bagi Perusahaan Distributor Terhadap Izin Edar Alat Kesehatan: Legal Certainty Analysis for Distributors Regarding Marketing Authorisation for Medical Devices - Endriyan Habilillah; Tahegga Primananda Alfath (Journal of Indonesian Comparative of Syari'ah Law, 2026)
This study aims to analyze the legal regulations governing the distribution of medical products within the framework of the Job Creation Law, as well as to examine the forms of legal protection and legal certainty for distribution companies whose distribution permit applications have been rejected. This study uses a normative legal method with a legislative and conceptual approach, focusing on the analysis of legislation in the fields of health, public administration, and risk-based business licensing. The results of the study show that although the Job Creation Law encourages the simplification of licensing procedures through the OSS-RBA system, in practice there are still problems in the form of inconsistencies in the application of authority between the central and local governments, overlapping technical regulations, and a lack of transparency regarding the reasons for rejecting distribution licenses. This situation has an impact on weak legal certainty and has the potential to harm business actors. Therefore, it is necessary to strengthen legal protection mechanisms through administrative and legal measures in administrative courts to ensure the principles of legal certainty, justice, and accountability in the medical device licensing system in Indonesia.